Implementation of Contextual Teaching and Learning (CTL) Model to Improve Mathematics Learning Outcomes on Line and Angle Material in Grades VII 6 SMP Negeri 1 Tapa - Siska Novrianti Abdullah; Majid Majid; Bertu Rianto Takaendengan; Putri Ekawaty Kobandaha (JEMS: Jurnal Edukasi Matematika dan Sains, 2025)
This study aims to improve mathematics learning outcomes through the implementation of the Contextual Teaching and Learning (CTL) learning model online and susdut material in grades VII-6 of SMP Negeri 1 Tapa totaling 20 people using the class action research method.  The data collection techniques used in this study are teacher conservation, student observation and student learning outcomes covering three domains, namely affective, psychomotor, and cognitive shutter. The results of data analysis showed an increase in mathematics learning outcomes in the good and very good categories with a percentage of 87.50% for teacher activities, 89.47% for student activities, and for learning hasl each affective domain reached 89%, psychomotor realm 85% and affective realm 90%. The implication of this research is that it needs the implementation of the Contextual Teaching and Learning (CTL) learning model in improving mathematics learning outcomes.